ANTIDIABETIC ACTIVITY OF NIGELLA SATIVA L. SEED POWDER AND ITS COMBINATION WITH GLICLAZIDE IN ALLOXAN INDUCED DIABETIC MICE - I. K., Adnyana; J. I., Sigit; S. A., Asad (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: In Indonesia, Nigella sativa (NS) has been widely used for the treatment of diabetes mellitus. The aim of this study was to evaluate the antidiabetic activity of its seed powder and its combination with gliclazide. Methods: NS was used in seed powder suspension form. At study's begin, Oral Glucose Tolerance Test (OGTT) was performed. And then the mice were induced with 60 mg/kg alloxan intravenously and were treated with 1300 mg/kg NS (NS1), 2000 mg/kg NS (NS2), 0,65 mg/kg gliclazide, and combination of NS1-gliclazide that administered orally for 3 weeks. NS1 was also administered daily to mice induced high-fat emulsion for 3 weeks. Results: The results showed that in OGTT, NS1 and NS2 inhibit the elevation of plasma glucose level after administering glucose. In mice induced alloxan, plasma glucose level in both NS1 and NS2 was significantly lower than diabetic control and gliclazide group. And NS2 showed more significantly less damage in Langerhans than the other groups. The combination did not showed a better effect than the single use. In mice induced high-fat emulsion, NSI improved the sensitivity of insulin by increasing KITT. Conclusion: The results suggest that NS has an antidiabetic activity by increasing insulin production and improving sensitivity of insulin. The combination NS with gliclazide was probably antagonism.